Significance of Molecular Dynamics Simulations for Life Sciences. Issue 8 (8th August 2014) - Karplus, Martin; Lavery, Richard
Abstract This article illustrates by examples the limited acceptance by biologists of predictions made with molecular dynamics simulations of biomolecules. Its purpose is to increase the awareness of biologists of the contribution that simulations can make to our understanding of biomolecule function.